Analisis Efektivitas Sosialisasi Perpajakan Dalam Rangka Meningkatkan Kepatuhan Wajib Pajak Usaha Mikro Kecil Dan Menengah (UMKM) di KPP Pratama Jakarta Sawah Besar Satu - Andrayanti, Iin; Denada, Adella; Prehantio, Tri Waluyo; Amalia, Laila (CV ODIS, 2025)
This study analyzes the effectiveness of tax outreach in improving taxpayer compliance among Micro, Small, and Medium Enterprises (MSMEs) at the Jakarta Sawah Besar Satu Tax Office (KPP Pratama). Using descriptive qualitative methods, data was obtained through interviews, observation, and documentation. The results indicate that the effectiveness of tax outreach has not been fully achieved, influenced by factors such as the large number of new provisions, diverse taxpayer backgrounds, difficulties in reaching taxpayers due to incomplete data, and limited tax knowledge. To overcome these obstacles, direct and indirect education through mass media, tailoring materials to taxpayer needs, reminders, and in-person visits were conducted. These findings emphasize the importance of an intensive and adaptive outreach strategy to improve MSME tax compliance